2019
DOI: 10.1371/journal.pgen.1008107
|View full text |Cite
|
Sign up to set email alerts
|

Risk of spontaneous preterm birth and fetal growth associates with fetal SLIT2

Abstract: Spontaneous preterm birth (SPTB) is the leading cause of neonatal death and morbidity worldwide. Both maternal and fetal genetic factors likely contribute to SPTB. We performed a genome-wide association study (GWAS) on a population of Finnish origin that included 247 infants with SPTB (gestational age [GA] < 36 weeks) and 419 term controls (GA 38–41 weeks). The strongest signal came within the gene encoding slit guidance ligand 2 ( SLIT2 ; rs116461311, minor allele frequency 0.05, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 87 publications
0
61
2
Order By: Relevance
“…A genome-wide association study (GWAS) has found that slit guidance ligand 2-roundabout guidance receptor 1 (SLIT2-ROBO1) signaling in trophoblasts is associated with PTB and that higher mRNA levels of SLIT2 and ROBO1 are detected in the basal plate of placentas from PTB samples [148]. Interestingly, knockdown of ROBO1 in trophoblast- derived cells upregulated 6 of 10 pregnancy-specific glycoproteins (PSGs).…”
Section: Glycosylation In Pregnancy Term and Preterm Labormentioning
confidence: 99%
“…A genome-wide association study (GWAS) has found that slit guidance ligand 2-roundabout guidance receptor 1 (SLIT2-ROBO1) signaling in trophoblasts is associated with PTB and that higher mRNA levels of SLIT2 and ROBO1 are detected in the basal plate of placentas from PTB samples [148]. Interestingly, knockdown of ROBO1 in trophoblast- derived cells upregulated 6 of 10 pregnancy-specific glycoproteins (PSGs).…”
Section: Glycosylation In Pregnancy Term and Preterm Labormentioning
confidence: 99%
“…A similar approach was also used in a genome wide association study of early preterm and term infants. Several significant variants near the gene SLIT2 were identified that overlaps regions of DNase hypersensitivity, suggesting regulatory activity, in several fetal tissues including the amnion (Tiensuu et al, 2019).…”
Section: Genetic Studies Of Fetal Membranesmentioning
confidence: 99%
“…In one new study, mutations in the gene that codes for SLIT2, a protein expressed in fetal cells in placentas and involved in directing the growth of the fetal nervous system, are shown to be associated with the risk of SPTB (Tiensuu et al, 2019). In addition, both SLIT2 and its receptor roundabout guidance receptor 1 (ROBO1) were expressed in placental cells, and mRNA levels were higher in placentas from spontaneous preterm deliveries than those in a control group of infants born at full term.…”
Section: The Studiesmentioning
confidence: 99%